Embodiment and agency in a digital world - Gangopadhyay, Nivedita; Pichler, Alois (Frontiers in Psychology, 2024)
We are agents and our agency is often best characterised in terms of embodied cognition. However, this is not to deny that there are cognitively significant ways of agentive engagement with the world that may be described without referring to our embodiment. In this paper we shall focus on the interplay between embodied agency and non-embodied agency or agency that may not be straightforwardly described in terms of embodied cognition in the context of interaction with digital technologies. In recent years a lot of our daily lives are coupled to the world via digital technologies. Yet how to understand the nature and evolution of our agency in the context of interacting with daily digital technologies is an open question. We propose to address this question by focusing on whether the steady development of digital technologies in our daily lives challenges the view that embodied agency is the de facto way of robustly engaging with the world and if embodied cognition is challenged then what is taking its place in scenarios where it was once dominant.